Risk Factors for Severe Acute Respiratory Syndrome Coronavirus 2 Infection in Homeless Shelters in Chicago, Illinois—March–May, 2020. (12th October 2020) - Ghinai, Isaac; Davis, Elizabeth S; Mayer, Stockton; Toews, Karrie-Ann; Huggett, Thomas D; Snow-Hill, Nyssa; Perez, Omar; Hayden, Mary K; Tehrani, Seena; Landi, A Justine; Crane, Stephanie; Bell, Elizabeth; et al.
Abstract: Background: People experiencing homelessness are at increased risk of coronavirus disease 2019 (COVID-19), but little is known about specific risk factors for infection within homeless shelters. Methods: We performed widespread severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) polymerase chain reaction testing and collected risk factor information at all homeless shelters in Chicago with at least 1 reported case of COVID-19 (n = 21). Multivariable, mixed-effects log-binomial models were built to estimate adjusted prevalence ratios (aPRs) for SARS-CoV-2 infection for both individual- and facility-level risk factors. Results: During March 1 to May 1, 2020, 1717 shelter residents and staff were tested for SARS-CoV-2; 472 (27%) persons tested positive. Prevalence of infection was higher for residents (431 of 1435, 30%) than for staff (41 of 282, 15%) (prevalence ratio = 2.52; 95% confidence interval [CI], 1.78–3.58). The majority of residents with SARS-CoV-2 infection (293 of 406 with available information about symptoms, 72%) reported no symptoms at the time of specimen collection or within the following 2 weeks. Among residents, sharing a room with a large number of people was associated with increased likelihood of infection (aPR for sharing with >20 people compared with single rooms = 1.76; 95% CI, 1.11–2.80), and current smoking was associated with reduced likelihood of infection (aPR = 0.71; 95% CI, 0.60–0.85). At the facility level, a higher proportion of residents leaving and returning each day was associated with increased prevalence (aPR = 1.08; 95% CI, 1.01–1.16), whereas an increase in the number of private bathrooms was associated with reduced prevalence (aPR for 1 additional private bathroom per 100 people = 0.92; 95% CI, 0.87–0.98). Conclusions: We identified a high prevalence of SARS-CoV-2 infections in homeless shelters. Reducing the number of residents sharing dormitories might reduce the likelihood of SARS-CoV-2 infection. When community transmission is high, limiting movement of persons experiencing homelessness into and out of shelters might also be beneficial. Abstract : Risk factors for SARS-CoV-2 infection included being a homeless shelter resident compared to a staff member, sleeping in a room with large numbers of other residents, and residing in a shelter where many residents leave and return each day.